Cololejeunea nanhutashanensis (Lejeuneaceae), a new species from Taiwan - Yang, Jia-Dong; Lin, Shan-Hsiung (Phytotaxa, 2014)
Cololejeunea nanhutashanensis is described as a new species from Taiwan. The new taxon is included in subgenus Cololejeunea (Spruce) Schiffner, and characterized mainly by its ovate to broadly ovate leaves with obtuse apex; large leaf lobule, 2/3–3/4 of lobe length; lobule with 2 teeth, separated by 2–4 cells from each other; stylus 5–16 cells long, 1–3 seriate; leaf cells thin-walled with large trigones and hemispherical dorsal protrusions; androecia terminal on short lateral branches with male bracts in 3–5 pairs; female bracts large, bract lobule almost as long as bract lobe; perianth obovate to oblong, 5-keeled, with dorsal protrusions on upper 1/3 surface. Its main characters are illustrated, and its distinction from other closely related consubgeneric species is discussed.